Ilizarov-assisted periosteal distraction for refractory arteriovenous malformation ulcers: first clinical report in Asia - Xiangyi Wu; Ren Cai; Mao Ye; Xitao Yang; Dachuan Sun; Yifeng Han; Xindong Fan; Jiaxue Zhu (Hereditas)
Abstract Refractory ulcers caused by high-flow arteriovenous malformations (AVMs) pose significant therapeutic challenges due to persistent tissue ischemia and shear stress-induced graft failure. Traditional embolization or flap reconstruction strategies often yield suboptimal outcomes, particularly in weight-bearing regions. We present a 28-year-old female with a non-healing dorsal foot AVM ulcer despite multiple embolizations and radical toe amputations. Genetic testing revealed a KRAS mutation, confirming a somatic etiology of AVM. After a debridement and local flap repair, we employed Ilizarov-assisted periosteal distraction to improve local perfusion. 75% of the wound epithelialized and the infection resolved within 4 weeks postoperatively, with granulation tissue covering the remainder. This case highlights the mechanobiological advantages of Ilizarov-based neovascular stimulation in AVM-related ischemic ulcers.